Gastric infiltration of hepatic sarcomatoid carcinoma: A case report and literature review - Ma, Shuoshuo; Zhang, Dengyong; Zhao, Guanru; Ding, Sheng; Wu, Qiong; Zhang, Xueli; Lu, Zheng (Frontiers in Surgery, 2023)
Background: Hepatic sarcomatoid carcinoma (HSC), an extremely rare malignant tumor in clinical practice, mostly occurs in the right lobe and rarely in the left lobe of the liver. This paper reports a case of sarcomatoid carcinoma that occurred in the left outer lobe of the liver, accompanied by gastric stromal tumors (GSTs) of the greater curvature of the stomach, and the patient developed gastric metastasis of liver sarcomatoid carcinoma in the later stage. Case presentation: A 63-year-old male patient was diagnosed with both HSC and GST. With fever as the main clinical manifestation, the liver malignant tumor was detected after he underwent abdominal computer tomography (CT) and ultrasound-guided percutaneous liver biopsy at the local hospital. The patient came to our hospital for further treatment. During the next electronic gastroscopy, we found multiple submucosal tumors (SMT) in the stomach. Without multiple metastases in other parts, we performed left hepatic lobe resection with gastric partial resection, and the postoperative pathology determined the presence of HSC and GST. One month after surgery, the patient felt well, and the imaging examination found no obvious space-occupying lesions in other areas. Unfortunately, four months later, the patient showed pain in the upper left abdomen and found metastases in the stomach. We performed the operation on him again, and the patient recovered well after the operation. The patient was still alive at the time of writing this paper. Conclusion: Hepatic sarcomatoid carcinoma lacks characteristic clinical manifestations and is highly malignant. Surgery is the first choice for the treatment of patients with HSC. For sarcomatoid cancer that occurs in the left lobe of the liver, we need to be highly vigilant against the tumor's invasion of the stomach tissue, especially when the tumor breaks through the capsule of the liver. In addition, during the operation, doctors need to perform delicate operations to avoid dissemination and metastasis of the gastrointestinal tract.